What is special about the human body?. (3rd July 2015) - Fox, Marie
ABSTRACT: UK health law has recently become more attentive to corporeality and embodiment, with implications for how legal subjectivity is understood. Yet, the body of health law remains a distinctively human body. Non-human bodies figure only at its margins, in its response to technologies such as xenotransplantation which expose the fault-lines surrounding human bodies. I aim to further trouble this boundary by exploring the liminal, queer and posthuman figure of the 'trans-embryo'. I argue that these extracorporeal embryos carry significant potential to disrupt our understandings of the human and of the legal subject. Eschewing personhood arguments, I aim to recast trans-embryos as embodied and relational products of human and animal reproductive labour. I conclude that, so viewed, they facilitate a new understanding of the corporeality and vulnerability we share with animals, thereby challenging human exceptionalism and the perceived distinctiveness of human bodies. Consequently, new forms of legal subjectivity which reflect an inter-species ethics are required.